Advances in the Surgical Treatment of Neuroblastoma: A Review - Murphy, Jennifer M.; La Quaglia, Michael P. (European Journal of Pediatric Surgery, 2014)
Neuroblastoma prognosis varies tremendously based on the stage and biologic features of the tumor. Treatment varies depending on the risk group and can range from surgery alone for stage 1 tumors to aggressive multimodality treatment for MYCN-amplified tumors. Although surgery plays a role in the diagnosis and management of all stages of neuroblastoma, the importance of that role, especially the extent of resection, in high-risk neuroblastoma continues to evolve. In the past five years, there have been several advances in neuroblastoma surgery. Studies have demonstrated that patients with low-risk disease can be treated with surgery alone, and in a subset of patients who are neonatally diagnosed with adrenal tumors, surgery can be avoided in 80%. Recent abstracts have supported a role for >90% resection of the primary tumor in high-risk patients. This article also reviews the surgical approaches to difficult thoracic and abdominal tumors, as well as the role for minimally invasive surgery in the management of localized neuroblastoma.
Keywords: neuroblastoma; abdominal tumors; MYCN